Amorphous mixtures of albendazole with carboxylic acids and evaluation of their anthelmintic activity - I. A. Arkhipov; S. S. Khalikov; A. I. Varlamova; M. M. Ilyin; B. V. Lokshin; M. S. Khalikov; I. M. Odoevskaya (Российский паразитологический журнал, 2025)
The purpose of the research is modification of albendazole (ABZ) properties due to the formation amorphous mixtures with carboxylic acids and evaluation of their anthelmintic activity.Materials and methods. Amorphous mixtures of ABZ with carboxylic acids (citric, succinic, p-toluenesulfonic and oxalic) were obtained according to the method described by Shete A.S. et al. (2019) with minor modification and expansion of the spectrum of carboxylic acids. The obtained amorphous mixtures were characterized by water solubility and ABZ content by high-performance liquid chromatography. IR spectroscopy method was used to prove the formation of target products. The anthelmintic activity of ABZ amorphous mixtures with organic acids in 1 : 1 ratio was studied on 80 white mice experimentally infected with Trichinella spiralis. Various mixtures of anthelmintic were administered into the stomach of mice of experimental groups at a dose of 2 mg/kg of active substance (AS). ABZ substance was used as a basic drug at a dose of 2 mg/kg of AS. The animals of the control group did not receive the drugs. The animals were sacrificed by cervical dislocation on the fourth day after drugs administration. The anthelmintic activity of the drugs was assessed based on the results of the helminthological necropsy of the mice intestines, and the efficacy was calculated according to the “control test”.Results and discussion. An increase in the solubility of the obtained amorphous mixtures of ABZ with carboxylic acids was established, the highest indices were noted for mixtures of ABZ with citric and para-toluenesulfonic acids. IR analysis confirmed the formation of salt-like products. It was established that the efficacy of amorphous mixtures of ABZ is higher than the activity of the basic drug (31.22%) in experimental trichinellosis, in particular, salt forms of albendazole with p-toluenesulfonic acid obtained after joint grinding showed 69.25%; amorphous mixtures with citric acid obtained after boiling in isopropanol showed 68.24% activity. Thus, when ABZ is modified with organic acids, its physicochemical properties change and its biological activity changes towards an increase.